EDUCATION FOR LEISURE IN ELEMENTARY SCHOOL: THE USE OF COMIC BOOKS IN PHYSICAL EDUCATION CLASSES - Lopes da Silva, Cinthia; Rossi Filho, Silvio; Pinto Costa da Silva, Priscilla; Schwartz, Gisele Maria; Ferreira de Souza, Marcio; dos Santos Souza, Adalberto; Scalzitti, Adriano; Pillon, Rosiane; Ferreira da Silva, Luciene; Capellini Rigoni, Ana Carolina (APRENDER - Caderno de Filosofia e Psicologia da Educação, 2020)
In Brazil, many students dislike Physical Education classes because of content repetition, dissatisfactory curricular organization, among other factors. This work aims at assessing the efficiency of a proposal for Physical Education classes, which includes contents of physical activities and the use of comic books. This is a qualitative study and both bibliographic and field researches were carried out. Ten classes were held to a group of ninth graders from a public school in the city of Piracicaba/SP/Brazil. We found that the use of comic books as a teaching resource is effective: it portrays the experiences that the students, felt and mediated through their “rational” and “sensitive” knowledge about physical activities.